Wewenang Pelaksanaan Diskresi Kepolisian Dalam Upaya Penegakan Hukum (Tinjauan Dari Perspektif Yuridis Normatif) - I Wayan Wisadnya (Jurnal Ilmiah Raad Kertha, 2020)
Problems regarding Law infoscment (law enforcement), especially in the police discretion, this is not just an option for the police, but is an important and inevitable part of carrying out law enforcement tasks, with the aim of reducing the crime rate, in order to create a safe situation. and orderly in the midst of society and conducive conditions. In the book Black Law Dictionary comes from the Dutch Discretionary language which means Wisdom in terms of deciding an action not based on the provisions of regulations, laws or applicable law, but on the basis of wisdom, consideration or justice. The authority of the National Police in exercising police discretion in law enforcement efforts is carried out by acting in the public interest based on self-assessment and only in very necessary circumstances, with due observance of laws and regulations, such as Law No.2 of 2002 concerning the Indonesian National Police, the Book of Law In addition, the Criminal Procedure Code (KUHAP) and Perkap No.1 / 2009 must also uphold human rights and the Police Professional Code of Ethics. Therefore, problems in the field can be identified, namely: what is the authority of the Police in implementing discretion? and what is the law enforcement effort?, then this study uses the Normative juridical approach, namely an approach based on statutory regulations, as well as legal materials that apply as positive law in Indonesia. So the conclusion is that the authority of the police in implementing police discretion in the effort to enforce the law is carried out by acting alone in the public interest based on self-assessment and only in very urgent situations by taking into account statutory regulations, such as the Police Law, KUHAP and Perkap (Praturan Kapolri No.1 2009), and Upholding Human Rights and the Professional Code of Ethics for the Indonesian National Police.